Cucumis sativus (cucumber): a review on its pharmacological activity - Sahu, Tripti; Sahu, Jyoti (Journal of Applied Pharmaceutical Research, 2015)
Medicinal plants have been used for centuries, and numerous cultures still rely on plants for their primary health care needs. In the recent past there has been a tremendous increase in the use of plant based health products in developing as well as developed countries resulting in an exponential growth of herbal products globally. The present article gives an account of such a medicinally important of Cucumis sativus belonging to family Cucurbitaceae which comprise both wild and cultivated species and is consumed in different ways like vegetable and salads, but less is known about its medicinal importance. Phytochemical analysis of these plants confirms the presence of various phytochemicals like tannins, cardiac glycosides, terpenoides, carbohydrates, resins, Saponins and phytosterols. While other phtochemicals like alkaloids, flavonoids, glycosides, steroidal terpenes and phylobatamins were found to be cucumber fruits. The plant exhibits various pharmacological activities such as anti-bacterial activity, antifungal activity, cytotoxic activity, Antacid & Carminative activity, Activity against ulcerative colitis ,Hepetoprotective activity, Hypoglycemic and Hypolipidemic activity, Wound healing activity etc. A study on safety profile suggests the plant to be safe for its therapeutic uses.